Privatizációs dilemma a budapesti bérlakásszektorba (Szociológiai Szemle, 2024)
The local self-governments face a very difficult dilemma when they have to choose between selling or retaining the rented flats, between raising the prices or squandering the flats, in one word, when they work out the details of how to manage the local flat-stock. What should the role of the rented flats be, how should those households be defended which are characterized by a low level of income and how should the decayed flats be restored? At the same time a similarly difficult dilemma is to be faced by the households themselves: they should decide upon whether to buy their flats from the self-governments at the present cheap price (while they have only very meagre information concerning the real condition of the building or the necessary expenses of maintenance or full restoration); if they decide not to buy the flats, they are bound to face as tenants unforeseen problems in the future. The authors try in this paper to survey the situation and the alternatives of the two main actors of the privatization process, i.e. of the local self-governments and the tenants, on the basis of empirical questionnaires concerning the privatization of flats in Budapest in 1992.